Structure for individual authentication and its manufacturing method

JP7612178B2Active Publication Date: 2025-01-14SHIN ETSU CHEMICAL CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024003885
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-01-15
Publication Date
2025-01-14
Estimated Expiration
2040-05-26

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、ナノピラーの変形の種類や程度で、グレースケールを構成することができ、また、変形後のピラーパターンの態様は、実質的に無限大であるので、本発明の個体認証用構造体を用いることにより、優れた個別性及び耐クローン性で、人工物による個体認証が可能である。また、本発明の個体認証用構造体では、合成石英ガラスは、通常、金属不純物濃度が1ppm以下と、極めて純度が高いことから、太陽光、紫外線、温度変化等の外部環境による変形、変色、劣化等の変質がほとんどなく、優れた耐候性や長期安定性及び高い長期信頼性が得られる。更に、地球環境だけでなく、宇宙空間や惑星の環境下においても、優れた耐候性や長期安定性及び高い長期信頼性が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612178000003
    Figure 0007612178000003
  • Figure 0007612178000004
    Figure 0007612178000004
  • Figure 0007612178000005
    Figure 0007612178000005
Patent Text Reader

Abstract

SOLUTION: Provided is an individual authentication structure in which a pillar pattern area including a plurality of nano pillars formed of synthetic quartz glass is formed on at least a part of a surface part of a synthetic quartz glass substrate, an indentation elasticity modulus of the nano pillar in the pillar pattern area, measured by a nano-indentation method, is 35 to 100 GPa, and the nano pillar is plastically deformed.EFFECT: A grayscale can be constituted with a type or a degree of deformation of a nano pillar. Since a state of a pillar pattern after deformation is substantially infinite, individual authentication by an artifact with excellent individual property and cloning resistance is possible by using the individual authentication structure. Furthermore, in the individual authentication structure, the synthetic quartz glass usually has extremely high purity with a metal impurity concentration of 1 ppm or less. Thus, there is almost no change in quality such as deformation, discoloration and degradation caused by an external environment such as sunlight, ultraviolet rays and temperature change. Therefore, excellent weather resistance, long-term stability and high long-term reliability can be obtained.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an individual authentication structure used for individual authentication, which performs authentication by utilizing a unique feature formed on an individual, which is an artificial object, and a method for manufacturing the same. [Background technology]

[0002] Biometric technology, which authenticates individuals using biometric information unique to each individual, has been put to practical use in various technical fields. Biometric information includes physical characteristics such as fingerprints, irises, and veins, as well as behavioral characteristics such as voiceprints and handwriting, and is used for user authentication of smartphones and cash cards, authentication of computer login authority, etc. In recent years, progress has been made in the development of artifactmetrics technology, which authenticates artifacts that have unique information similar to such biometric information, using that unique information.

[0003] Artifact-metrics technology is a promising technique for improving the safety and reliability of items that require counterfeit prevention, such as certificates and cash cards. Artifacts used in this artifact-metrics technology are required to possess physical properties unique to each individual, including individuality, read stability, durability, and clone resistance.

[0004] For example, a technology has been proposed that uses artificial patterns with extremely low reproducibility, such as the light reflection pattern of granular matter incorporated into a medium such as a credit card, the magnetic pattern of a magnetic fiber, a randomly recorded magnetic pattern, a random magnetic pattern of a magnetic stripe, a random charge amount pattern of a memory cell, and the resonance pattern of a conductive fiber, as unique information. Furthermore, Japanese Patent Laid-Open Publication No. 2014-59377 (Patent Document 1) describes an artifact metrics structure obtained by forming an active energy ray-sensitive resist coating on a substrate, irradiating the substrate with active energy rays, and then performing a development process to form a pattern. Then, an external force is applied to collapse part of the pattern to form a pattern aggregate, and the pattern aggregate exhibits clone resistance. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Laid-Open No. 2014-59377 Summary of the Invention [Problem to be solved by the invention]

[0006] However, while many conventional artificial patterns can be used as artificial objects to provide unique information for authentication, they have the problem of being difficult to incorporate into IC cards and the like due to the difficulty of forming them into extremely small chips. Furthermore, the pattern deformation in the resist structure described in JP 2014-59377 A is limited to three types: tilt, collapse, and slippage, which is insufficient in terms of clone resistance. Furthermore, sunlight, ultraviolet rays, temperature changes, etc. may cause deformation, discoloration, degradation, and other alterations, resulting in insufficient weather resistance and long-term stability, and low long-term reliability. Furthermore, there is a demand for an individual authentication structure that is excellent in weather resistance and long-term stability and can be used not only in terrestrial environments but also in outer space and planetary environments, contributing to long-term reliable artificial metrics technology.

[0007] The present invention has been made in view of the above circumstances, and aims to provide a structure for individual authentication having a fine artificial pattern that has excellent clone resistance and weather resistance, and has long-term reliability. [Means for solving the problem]

[0008] As a result of intensive research to achieve the above-mentioned object, the inventors discovered that using plastically deforming nanopillars formed from synthetic quartz glass and utilizing a pillar pattern containing the plastically deformed nanopillars for identification is effective for individual authentication using artificial objects, and that an individual authentication structure in which a pillar pattern area containing multiple nanopillars formed from synthetic quartz glass is formed on at least a portion of the surface of a synthetic quartz glass substrate, and in which the nanopillars have a predetermined indentation elastic modulus, is a structure that enables individual authentication with excellent clone resistance and weather resistance and high long-term reliability, leading to the present invention.

[0009] Therefore, the present invention provides the following structure for individual authentication and a method for manufacturing the same. 1. A structure for individual authentication in which a pillar pattern region including a plurality of nanopillars formed of synthetic silica glass is formed on at least a portion of the surface of a synthetic silica glass substrate, Only the nanopillars are formed as microstructures protruding from a base portion of the synthetic quartz glass substrate on a surface portion of the synthetic quartz glass substrate, In the pillar pattern region, the indentation elastic modulus of the nanopillars measured by a nanoindentation method is 35 to 100 GPa, A structure for individual authentication, wherein the nanopillars undergo plastic deformation. 2. A structure for individual authentication in which a pillar pattern region including a plurality of nanopillars formed of synthetic silica glass is formed on at least a portion of the surface of a synthetic silica glass substrate, the nanopillars have a cylindrical shape, an elliptical cylindrical shape, a truncated pyramid shape, a truncated cone shape, a truncated elliptical cone shape, an inverted truncated pyramid shape, an inverted truncated cone shape, or an inverted truncated elliptical cone shape; In the pillar pattern region, the indentation elastic modulus of the nanopillars measured by a nanoindentation method is 35 to 100 GPa, A structure for individual authentication, wherein the nanopillars undergo plastic deformation. 3. The structure for individual authentication according to 1 or 2, wherein the arrangement of the nanopillars formed in the pillar pattern region is a regular arrangement in which the pillars are arranged at a constant period. 4. The structure for individual authentication according to 3, wherein the period of the regular arrangement is 20 nm or more and 1,500 nm or less. 5. The structure for individual authentication according to any one of 1 to 4, wherein the height H of the nanopillar is 20 to 1,500 nm, the width W is 10 to 500 nm, and the aspect ratio (H / W) is 0.5 to 6. 6. The structure for individual authentication according to any one of 1 to 5, wherein the nanopillars are formed integrally with the base portion of a synthetic quartz glass substrate. 7. The structure for individual authentication according to any one of 1 to 6, in which a pillar pattern including plastically deformed nanopillars is used for identification. 8. A structure for individual authentication in which a pillar pattern region including a plurality of nanopillars formed of synthetic silica glass is formed on at least a portion of the surface of a synthetic silica glass substrate, In the pillar pattern region, the indentation elastic modulus of the nanopillars measured by a nanoindentation method is 35 to 100 GPa, A structure for individual authentication, characterized in that the pillar pattern region includes nanopillars that have been pressed in the height direction and plastically deformed. 9. The structure for individual authentication according to 8, wherein the nanopillars are formed integrally with the base portion of the synthetic quartz glass substrate. 10. A method for manufacturing an individual authentication structure according to any one of 1 to 7, forming an inorganic film on a surface of a synthetic quartz glass substrate on which the pillar pattern region is to be formed; forming an organic film on the inorganic film; patterning the organic film to form an organic film pattern on the inorganic film; forming an inorganic film pattern by etching the inorganic film using the organic film pattern as an etching mask; a step of etching a surface portion of the synthetic quartz glass substrate using the organic film pattern and / or the inorganic film pattern as an etching mask to form the pillar pattern region; removing the organic film pattern and / or the inorganic film pattern; A method for manufacturing an individual authentication structure, comprising: 11. A method for manufacturing an individual authentication structure according to any one of 1 to 7, forming an organic film on a surface of the synthetic quartz glass substrate on which the pillar pattern region is to be formed; a step of patterning the organic film to form an organic film pattern on a surface of the synthetic quartz glass substrate on which the pillar pattern region is to be formed; forming an inorganic film on the organic film pattern and the exposed surface of the synthetic quartz glass substrate; removing the organic film pattern together with an inorganic film formed on the organic film pattern; a step of etching a surface portion of the synthetic quartz glass substrate using an inorganic film pattern formed by an inorganic film formed on the surface of the synthetic quartz glass substrate as an etching mask to form the pillar pattern region; removing the inorganic film pattern A method for manufacturing an individual authentication structure, comprising: 12. The manufacturing method according to 10 or 11, wherein in the step of forming the organic film pattern, the organic film pattern is formed by electron beam lithography, photolithography or nanoimprint lithography. The present invention also relates to the following individual authentication structure, manufacturing method thereof, and individual authentication method. [1] A structure for individual authentication in which a pillar pattern region including a plurality of nanopillars formed of synthetic silica glass is formed on at least a portion of the surface of a synthetic silica glass substrate, In the pillar pattern region, the indentation elastic modulus of the nanopillars measured by a nanoindentation method is 35 to 100 GPa, A structure for individual authentication, wherein the nanopillars undergo plastic deformation. [2] The structure for individual authentication according to [1], wherein the height H of the nanopillar is 20 to 1,500 nm, the width W is 10 to 500 nm, and the aspect ratio (H / W) is 0.5 to 6. [3]. A method for manufacturing the structure for individual authentication according to [1] or [2], forming an inorganic film on a surface of a synthetic quartz glass substrate on which the pillar pattern region is to be formed; forming an organic film on the inorganic film; patterning the organic film to form an organic film pattern on the inorganic film; forming an inorganic film pattern by etching the inorganic film using the organic film pattern as an etching mask; a step of etching a surface portion of the synthetic quartz glass substrate using the organic film pattern and / or the inorganic film pattern as an etching mask to form the pillar pattern region; removing the organic film pattern and / or the inorganic film pattern; A method for manufacturing an individual authentication structure, comprising: [4]. A method for manufacturing the structure for individual authentication according to [1] or [2], forming an organic film on a surface of the synthetic quartz glass substrate on which the pillar pattern region is to be formed; a step of patterning the organic film to form an organic film pattern on a surface of the synthetic quartz glass substrate on which the pillar pattern region is to be formed; forming an inorganic film on the organic film pattern and the exposed surface of the synthetic quartz glass substrate; removing the organic film pattern together with the inorganic film formed on the organic film pattern; a step of etching a surface portion of the synthetic quartz glass substrate using an inorganic film pattern formed by an inorganic film formed on the surface of the synthetic quartz glass substrate as an etching mask to form the pillar pattern region; removing the inorganic film pattern A method for manufacturing an individual authentication structure, comprising: [5] The manufacturing method according to [3] or [4], wherein in the step of forming the organic film pattern, the organic film pattern is formed by electron beam lithography, photolithography, or nanoimprint lithography. [6]. An individual authentication method characterized by pressing at least some of the nanopillars formed in the pillar pattern region of the individual authentication structure described in [1] or [2] in the height direction to plastically deform them, and identifying the pillar pattern including the deformed nanopillars. [Effects of the Invention]

[0010] According to the present invention, grayscales can be created by varying the type and degree of deformation of the nanopillars, and the shape of the pillar pattern after deformation is virtually infinite. Therefore, by using the identity authentication structure of the present invention, identity authentication using artificial objects is possible with excellent individuality and clone resistance. Furthermore, in the identity authentication structure of the present invention, the synthetic quartz glass is extremely pure, typically with a metal impurity concentration of 1 ppm or less, so there is almost no change in quality such as deformation, discoloration, or deterioration due to external environments such as sunlight, ultraviolet rays, and temperature changes, and excellent weather resistance, long-term stability, and high long-term reliability are obtained. Furthermore, excellent weather resistance, long-term stability, and high long-term reliability are obtained not only in the terrestrial environment but also in the environments of outer space and planets. [Brief explanation of the drawings]

[0011] [Figure 1] FIG. 1 is a plan view showing one embodiment of the arrangement of pillar pattern regions on a synthetic quartz glass substrate, (A) to (C) showing examples in which pillar pattern regions are provided in one place, three places, and five places, respectively. [Figure 2] FIG. 1 is a plan view showing one embodiment of an array of nanopillars formed within a pillar pattern region of a synthetic quartz glass substrate. [Figure 3] 1A and 1B are cross-sectional views showing one embodiment of the shape of the nanopillars, where (A) shows a cylindrical nanopillar and (B) shows a truncated cone nanopillar. [Figure 4] 1A and 1B are cross-sectional views showing one embodiment of the shape of nanopillars after plastic deformation, where (A) shows a barrel-shaped nanopillar and (B) shows a mushroom-shaped nanopillar. [Figure 5]1A and 1B are plan views showing one embodiment of the shape of nanopillars after plastic deformation, where (A) shows a nanopillar that is circular in plan view, (B) shows a nanopillar that is elliptical in plan view, and (C) shows a nanopillar that is circular in plan view and has a crack. [Figure 6] 1 is a scanning electron microscope image of a pillar pattern region of the individual authentication structure obtained in Example 1. [Figure 7] 1 is a scanning electron microscope image of a pillar pattern region of the individual authentication structure obtained in Example 2. [Figure 8] 10 is a scanning electron microscope image of a pillar pattern region of the individual authentication structure obtained in Example 3. [Figure 9] 10 is a scanning electron microscope image of a pillar pattern region of the individual authentication structure obtained in Example 4. [Figure 10] These are optical microscope images of the top surface of nanopillars in the pillar pattern region in Experimental Example 1, where (A) is before plastic deformation, (B) is after plastic deformation, and (C) is an image of (B) that has been converted (binarized) for image analysis. [Figure 11] 1 is a scanning electron microscope image of the top surface of a portion of the pillar pattern region where nanopillars have been plastically deformed in the individual authentication structure of Experimental Example 1. [Figure 12] These are atomic force microscope images of the portion of the pillar pattern region where the nanopillars in the individual authentication structure of Experimental Example 1 were plastically deformed. (A) is a top view before plastic deformation, (B) is a cross-sectional profile before plastic deformation, (C) is a top view after plastic deformation, and (D) is a cross-sectional profile after plastic deformation. [Figure 13] 1 is a scanning electron microscope image of a pillar pattern region of the individual authentication structure obtained in Comparative Example 1. [Figure 14] (A) is a scanning electron microscope image of the top surface of the portion of the individual authentication structure of Comparative Experimental Example 1 where the nanopillars in the pillar pattern region have been plastically deformed, and (B) is an image of (A) that has been converted (binarized) for image analysis. DETAILED DESCRIPTION OF THE INVENTION

[0012] The present invention will be described in more detail below. Hereinafter, embodiments of the present invention will be described with reference to the drawings. However, the drawings are schematic or conceptual, and the dimensions of each component, the size and ratio between components, etc. are not necessarily the same as those in reality. Furthermore, even when the same components, etc. are shown, the dimensions and ratios between them may be expressed differently depending on the drawing.

[0013] The structure for identity authentication of the present invention has a pillar pattern region including a plurality of nanopillars formed of synthetic silica glass formed on at least a portion of the surface of a synthetic silica glass substrate.

[0014] The synthetic quartz glass substrate used in the present invention can be obtained by forming a synthetic quartz glass ingot, which is produced by reacting a silica raw material compound such as a silane compound or a siloxane compound with an oxyhydrogen flame, into the desired shape, annealing it, slicing it to the desired thickness, lapping it, polishing the outer periphery as needed, and then rough polishing and precision polishing it.

[0015] The shape of the synthetic quartz glass substrate can be rectangular or other square, circular, or the like, for ease of manufacturing. For example, a square substrate with a side length of 10 to 300 mm is preferably used, while a circular glass substrate with a diameter of 10 to 300 mm is preferably used. The thickness of the synthetic quartz glass substrate is appropriately selected, but is preferably 10 μm or more, more preferably 50 μm or more, even more preferably 100 μm or more, and is preferably 300 mm or less, more preferably 100 mm or less, even more preferably 30 mm or less. Synthetic quartz glass substrates having the above-mentioned sizes, on which an individual authentication structure is formed on a portion of the surface thereof, may be, for example, a square substrate with a side length of 1 to 10 mm and a thickness of 1 mm or less, or a circular glass substrate with a diameter of 1 to 10 mm and a thickness of 1 mm or less, after which the substrate is diced to form a pillar pattern region containing a plurality of nanopillars formed from synthetic quartz glass. The shape of the synthetic quartz glass substrate to be processed is determined taking into consideration the dicing method, such as mechanical cutting, laser cutting, etc. The shape of the synthetic quartz glass substrate is also determined taking into consideration ease of handling when attaching the individual authentication structure to other members for identification.

[0016] The shape of the pillar pattern region present on at least a portion of the surface of the substrate depends on the measurement method and detection resolution used for authentication. When an electron microscope is used for measurement, the pillar pattern region preferably has a side length of 1 to 100 μm if it is rectangular, and a diameter of 1 to 100 μm if it is circular, depending on the imaging magnification. If the side length or diameter is less than 1 μm, the number of nanopillars in the individual authentication structure may be reduced, resulting in reduced individuality and clone resistance. Furthermore, if the side length or diameter exceeds 100 μm, they may be visually recognized, making it easier to identify the location of the individual authentication structure. When an atomic force microscope is used for measurement, the shape depends on the scannable range of the scanner, but preferably has a side length of 1 to 100 μm if it is rectangular, and a diameter of 1 to 100 μm if it is circular. When an optical microscope is used for measurement, it is preferable that the pillar pattern region has a side length of 10 μm to 2 mm if the shape is square, and a diameter of 10 μm to 2 mm if the shape is circular, although this depends on the imaging magnification.

[0017] Nanopillars are minute structures formed from synthetic silica glass and protruding from the base portion of the synthetic silica glass substrate. The pillar pattern region includes multiple nanopillars, each of which is arranged upright and spaced apart from other nanopillars. The nanopillars are usually formed integrally with the other portion (base portion) of the synthetic silica glass substrate.

[0018] 1 is a plan view showing one embodiment of the arrangement of pillar pattern regions on a synthetic quartz glass substrate, and in (A) to (C), one, three, and five pillar pattern regions 101 are provided on a synthetic quartz glass substrate 100, respectively. It is sufficient that at least one pillar pattern region is provided on a synthetic quartz glass substrate, and multiple pillar pattern regions may be provided. The shape of the pillar pattern region is not particularly limited, and examples include circles, ellipses, squares, rectangles, trapezoids, and triangles. However, the pillar pattern region may be an irregular shape that does not fall into any of these categories, or a combination of multiple shapes.

[0019] FIG. 2 is a plan view showing one embodiment of an arrangement of nanopillars formed in a pillar pattern region of a synthetic quartz glass substrate. Here, nanopillars 102 are arranged in a square lattice pattern within a pillar pattern region 101. The arrangement of nanopillars formed within the pillar pattern region is not particularly limited and may be a regular arrangement in which pillars are arranged at a fixed period, or a random arrangement. Examples of regular arrangements include an orthorhombic lattice pattern, a rectangular lattice pattern, a face-centered rectangular lattice pattern, a hexagonal lattice pattern, and a square lattice pattern. In the case of a regular arrangement, the period is not particularly limited, but is preferably 20 nm or more, more preferably 30 nm or more, and is preferably 1,500 nm or less, more preferably 1,000 nm or less.

[0020] 3A is a cross-sectional view showing one embodiment of the shape of the nanopillars, and (A) shows a cross-section of a cylindrical nanopillar 102a formed on a synthetic quartz glass substrate 100, while (B) shows a cross-section of a truncated conical nanopillar 102b formed on a synthetic quartz glass substrate 100. Specific shapes of the nanopillars include a rectangular column, a cylindrical column, an elliptical column, a truncated pyramid, a truncated cone, a truncated elliptical cone, an inverted truncated pyramid, an inverted truncated cone, and an inverted truncated elliptical cone, and a combination of multiple shapes may also be used.

[0021] In particular, in the pillar pattern region, the indentation modulus of the nanopillars, measured using a spherical indenter by nanoindentation, is 35 GPa or more, preferably 40 GPa or more, and 100 GPa or less, preferably 90 GPa or less, and more preferably 80 GPa or less. If the indentation modulus of the nanopillars is less than 35 GPa, the nanopillars are likely to chip when plastically deformed by being pressed, and nanopillar fragments separated from the nanopillars may interfere with individual authentication. On the other hand, if the indentation modulus of the nanopillars is greater than 100 GPa, it may be difficult to plastically deform the nanopillars by being pressed.

[0022] Indentation modulus E of nanopillars ITis the contact depth h obtained from the load-displacement curve obtained by the nanoindentation test. c , contact projected area A p and contact stiffness S and indenter elastic modulus E i , Poisson's ratio of the indenter ν i and the Poisson's ratio ν of the sample s The indentation modulus of the nanopillar, E IT is the composite elastic modulus E that includes the elastic deformation of the sample and the elastic deformation of the indenter. r The elastic modulus is calculated by taking only the sample into consideration, and specifically, it can be calculated by the following formula (1).

[0023]

number

[0024] Here, the composite elastic modulus E r is the contact depth h obtained from the load-displacement curve c , contact projected area A p and contact stiffness S, is given by the following formula (2).

[0025]

number

[0026] The height H of the nanopillar is preferably 20 nm or more, more preferably 30 nm or more, and even more preferably 80 nm or more, and preferably 1,500 nm or less, more preferably 1,000 nm or less, and even more preferably 500 nm or less. The width W of the nanopillar (particularly the width at the top) is preferably 10 nm or more, more preferably 20 nm or more, and even more preferably 40 nm or more, and preferably 500 nm or less, more preferably 300 nm or less, and even more preferably 140 nm or less. For example, if the height of the nanopillar is less than 20 nm and the width of the nanopillar is less than 10 nm, it may be difficult to determine the degree of deformation after plastic deformation of the nanopillar using an electron microscope or the like. On the other hand, if the height of the nanopillar is greater than 1,500 nm and the width of the nanopillar is greater than 500 nm, the number of pillars in the pillar pattern region will be small, which may be disadvantageous for individual authentication. The height of the nanopillar can be measured using an atomic force microscope, and the width of the nanopillar can be measured using an atomic force microscope or a scanning electron microscope.

[0027] The aspect ratio of the nanopillar (the ratio of height H to width (especially the width at the top) W (H / W)) is preferably 0.5 or more, more preferably 1 or more, and preferably 6 or less, more preferably 5 or less. If the aspect ratio (H / W) is lower than 0.5, it may be difficult to determine the degree of deformation after plastically deforming the nanopillar using an electron microscope or the like. On the other hand, if the aspect ratio (H / W) is higher than 6, the nanopillar is likely to chip when pressed and plastically deformed, and nanopillar fragments separated from the nanopillar may hinder individual authentication.

[0028] In the identity authentication structure of the present invention, the nanopillars must be capable of plastic deformation. This is because, in the identity authentication structure of the present invention, the difference between the nanopillars before and after plastic deformation is used as an identification element in identity authentication. The nanopillars are usually plastically deformed by pressing them in the height direction. This pressing can be performed, for example, by contacting a rigid body with the nanopillars (pillar pattern region) and pressing them in. In this way, an external force can be applied to the nanopillars, causing them to plastically deform.

[0029] The rigid body may be any body having a Young's modulus equal to or greater than that of the synthetic quartz glass forming the nanopillars to be plastically deformed, and suitable materials include diamond, sapphire, etc. The rigid body may be any body having a contact surface area equal to or greater than the area of ​​the top of the nanopillar, and suitable shapes include a sphere, a flat punch shape, and a cube corner shape. If the contact surface area of ​​the rigid body is smaller than the area of ​​the top of the nanopillar, chipping may easily occur in the nanopillar, and nanopillar fragments separated from the nanopillar may interfere with individual authentication.

[0030] Taking variations in the deformation pattern into consideration, the pressing speed is preferably 500 mN / s or less, more preferably 100 mN / s or less. Furthermore, from the viewpoint of achieving good identifiability in individual authentication, the pressing load is preferably 0.005 mN or more, more preferably 0.05 mN or more, even more preferably 0.5 mN or more, and is preferably 2,000 mN or less, more preferably 1,000 mN or less, even more preferably 500 mN or less. When plastically deforming the nanopillars, an indentation mark reflecting the shape of the rigid body is formed in the arrangement of the nanopillars in the pillar pattern region at the portion where the rigid body is contacted and pressed. For example, when the curved surface of a rigid body is contacted and pressed, a circular or elliptical indentation mark can be confirmed in the top view of the pillar pattern region when observed with an optical microscope or the like.

[0031] The shape of the pillar pattern region and the shape of a portion of the pillar pattern region where nanopillars plastically deformed by a spherical indenter are present during nanoindentation can be detected using bright-field, dark-field, or differential interference optical systems in an optical microscope. The shape of the portion of the pillar pattern region where the plastically deformed pillar pattern is present reflects the shape of the spherical indenter, and is therefore subject to individual recognition. Specific shapes include circular and elliptical. There may be multiple indentations made by the same spherical indenter, or multiple indentations made by different spherical indenters.

[0032] 4A and 4B are cross-sectional views showing one embodiment of the shape of nanopillars formed in a pillar pattern region of a synthetic quartz glass substrate after plastic deformation by pressing with a rigid body or the like. (A) shows a cross-section of a barrel-shaped nanopillar 102c formed on a synthetic quartz glass substrate 100, and (B) shows a cross-section of a mushroom-shaped nanopillar 102d formed on the synthetic quartz glass substrate 100. The barrel-shaped nanopillar 102c shown in FIG. 4A can be obtained, for example, by pressing and plastically deforming the cylindrical nanopillar 102a shown in FIG. 3A. On the other hand, the mushroom-shaped nanopillar 102d shown in FIG. 4B can be obtained, for example, by pressing and plastically deforming the truncated cone-shaped nanopillar 102b shown in FIG. 3B.

[0033] Figure 5 is a plan view showing one embodiment of the shape of a nanopillar formed in a pillar pattern region of a synthetic quartz glass substrate after plastic deformation by pressing with a rigid body or the like. (A) shows a nanopillar 102e formed in the pillar pattern region 101 that is circular in plan view, (B) shows a nanopillar 102f formed in the pillar pattern region 101 that is elliptical in plan view, and (C) shows a nanopillar 102g formed in the pillar pattern region 101 that is circular in plan view and has a crack that occurred on the nanopillar surface during plastic deformation. The nanopillars 102e and 102g shown in Figures 5(A) and 5(C) are circular in plan view and can be obtained by, for example, compressing and plastically deforming the cylindrical nanopillar 102a shown in Figure 3(A) and the truncated cone-shaped nanopillar 102b shown in Figure 3(B) in the nanopillar array shown in Figure 2. The nanopillars are circular in plan view and have a larger area than before plastic deformation. On the other hand, the nanopillar 102f shown in Figure 5(B) is elliptical in plan view and can be obtained by, for example, compressing and plastically deforming a nanopillar having an elliptical cylindrical shape, an elliptical truncated cone shape, or an inverted elliptical truncated cone shape. The nanopillars are elliptical in plan view and have a larger area than before plastic deformation.

[0034] 4 and 5 show the shapes of nanopillars that have been plastically deformed by uniformly pressing them with a rigid body, but the degree of plastic deformation of the nanopillars does not need to be uniform for all nanopillars. Furthermore, the shapes after plastic deformation are not limited to these, and may be a combination of two or more types.

[0035] At least some of the nanopillars formed in the pillar pattern region, for example, nanopillars present at specific positions in the individual authentication structure, are pressed in the height direction to plastically deform them, and the resulting pillar pattern containing the deformed nanopillars is identified, enabling individual authentication using artifacts. In this invention, the type and degree of deformation of the nanopillars serves as a grayscale, and the form of the pillar pattern after deformation is virtually infinite, resulting in excellent individuality and cloning resistance.

[0036] Identification factors for identifying pillar patterns include the degree of deformation, the number of individuals within the recognition field of view, pillar periodicity, etc. Specific identification factors for the degree of deformation include the shape, ellipticity, pillar diameter distribution, pillar height distribution, and number of cracks on the pillar surface within the deformed area. Specific identification factors for the number of individuals within the recognition field of view include the number of pillars within the deformed area and pillar number distribution, etc. Specific identification factors for pillar periodicity include the pillar position and pillar position distribution within the deformed area.

[0037] In addition, the synthetic quartz glass substrate of the individual authentication structure can be provided with alignment marks for individual authentication along with the pillar pattern area. If lithography, as described below, is used to form the nanopillars of the individual authentication structure, it is possible to provide the alignment marks for individual authentication in the same process as forming the pillar pattern area.

[0038] The pillar pattern region of the individual authentication structure of the present invention, which includes a plurality of nanopillars formed from synthetic quartz glass, can be manufactured by a lithography method such as electron beam lithography, photolithography, or nanoimprint lithography.

[0039] Specifically, this method includes, for example, (1) a step (first step) of forming an inorganic film on a surface of a synthetic quartz glass substrate on which a pillar pattern region is to be formed; (2) forming an organic film on the inorganic film (second step); (3) a step (third step) of patterning the organic film to form an organic film pattern on the inorganic film; (4) a step (fourth step) of etching the inorganic film using the organic film pattern as an etching mask to form an inorganic film pattern; (5) a step (fifth step) of etching the surface of the synthetic quartz glass substrate using the organic film pattern and / or the inorganic film pattern as an etching mask to form a pillar pattern region; (6) Step of removing the organic film pattern and / or the inorganic film pattern (sixth step) It can be produced by a method comprising:

[0040] In the first step, an inorganic film is typically formed on the entire surface of the synthetic quartz glass substrate where the pillar pattern region is to be formed. Examples of inorganic films include metal films and films of metal compounds such as metal nitrides, metal oxides, metal carbides, metal nitride oxides, metal nitride carbides, metal oxide carbides, and metal nitride oxycarbides. The metal film may be a simple film or an alloy film. Furthermore, the metal compound film may contain only one type of metal or a combination of two or more types of metals. Specific examples of metals include Ag, Al, Au, Cr, Cu, Mo, Ni, Ru, Si, Ta, Ti, and W. Among these inorganic films, from the viewpoint of ease of etching in the etching of the inorganic film in the fourth step, Cr film, Si film, Cr compound film, and Si compound film are preferred, and specific examples of Cr compounds include CrN, CrO, CrNO, and CrNOC (these formulas represent the constituent elements of the compound, and the ratio of each element is arbitrary), and specific examples of Si compounds include SiN (this formula represents the constituent elements of the compound, and the ratio of each element is arbitrary), etc. The film thickness of the inorganic film is preferably 200 nm or less, more preferably 50 nm or less, and preferably 2 nm or more.

[0041] The inorganic film can be formed by sputtering. Specifically, a metal target, a metal compound target, or the like is used as the target, and a rare gas such as argon gas, and optionally a reactive gas such as an oxygen-containing gas, a nitrogen-containing gas, or a carbon-containing gas, is used as the sputtering gas, and the inorganic film is formed on a synthetic quartz glass substrate in a sputtering apparatus. The power source may be either DC or AC, but when using a DC power source, it is preferable to apply measures to suppress arc generation.

[0042] In the second step, an organic film is formed on part or all of the surface of the inorganic film. Resist materials (photoresist materials) that are sensitive to desired activation energy rays, such as electron beams, X-rays, ultraviolet rays, excimer lasers (ArF, KrF, etc.), and high-pressure mercury lamps (i-rays, g-rays, etc.), are suitable for the organic film. While either positive or negative resist materials can be used, positive resist materials are preferred from the standpoints of precision and environmental friendliness. The thickness of the organic film can be selected from a range of 10 nm to several tens of μm, with thin films being preferred from the standpoint of resolution and thick films being preferred from the standpoint of etching resistance. Taking both factors into consideration, if wet etching is used for etching the surface of the synthetic quartz glass substrate in the fifth step, a thickness of approximately 0.5 to 5 μm is preferred, and if dry etching is used, a thickness of approximately 10 to 500 nm is preferred.

[0043] The organic film can be formed by spin coating, spray coating, slit coating, stencil printing, or other coating methods, but spin coating is preferred for achieving a more uniform coating. In spin coating, the coating is performed at a maximum rotation speed of 2,000 to 4,000 rpm, and baking (pre-baking) is performed after coating. The pre-baking temperature varies depending on the type of organic film material, but is preferably in the range of approximately 80 to 120°C.

[0044] In the third step, the organic film is patterned to form an organic film pattern on the inorganic film. Methods for forming the organic film pattern include electron beam lithography or photolithography, and nanoimprint lithography.

[0045] In the electron beam lithography method, an organic film pattern can be formed by drawing an organic film formed on an inorganic film using an electron beam drawing device and developing the pattern drawn on the organic film.In the photolithography method, an organic film pattern can be formed by exposing an organic film formed on an inorganic film using a photomask having predetermined light-shielding and non-light-shielding portions and developing the pattern transferred to the organic film.

[0046] The liquid used for development may be selected appropriately depending on the type of resist material. Suitable developers include, for example, aqueous alkaline solutions such as tetramethylammonium hydroxide (TMAH) and xylene-based organic solvents. After development, a rinse treatment with pure water or the like is performed to wash away any remaining developer and components derived from the resist material dissolved in the developer, followed by drying, thereby forming an organic film pattern on the inorganic film. After drying, post-baking may be performed to strengthen the organic film. Post-baking is performed at a temperature and / or for a time period at which the organic film is no longer photosensitive, and is preferably performed at a temperature higher than the pre-baking temperature before exposure (e.g., 130°C or higher).

[0047] In the nanoimprint lithography method, the concave-convex structure of an imprint mold having a predetermined concave-convex pattern is pressed against an organic film, the recesses of the mold are filled with a resist material, and the upper surface of the resist material is molded to have the shape of the concave-convex pattern.The organic film is hardened in this state, and then the imprint mold is separated from the hardened organic film, thereby forming an organic film pattern.

[0048] The concave-convex structure of the imprint mold is preferably pressed against the organic film under a helium gas atmosphere or a readily condensable gas atmosphere. A readily condensable gas atmosphere is a gas atmosphere that is easily liquefied by pressure when trapped in the mold voids. Such an atmosphere reduces the likelihood of bubble defects. Specific examples of such gases include 1,1,1,3,3-pentafluoropropane (PFP, HFC-245fa) and trans-1,3,3,3-tetrafluoropropene (TFP). Bubbles formed between the surface of the concave-convex structure of the imprint mold and the resist material can cause pattern defects in the organic film pattern. However, under a helium or readily condensable gas atmosphere, the helium gas or readily condensable gas that constitutes the bubbles dissolves into the resist material, preventing pattern defects. The organic film can be cured using a method appropriate for the curing type of the material that constitutes the organic film. For example, if the organic film material is UV-curable, a method such as irradiating the organic film with UV light via the imprint mold can be used.

[0049] After the imprint mold is separated from the cured organic film, a considerable thickness of the organic film (for example, 1 nm or more, particularly 5 nm or more, and 20 nm or less, particularly 10 nm or less) usually remains at the positions of the organic film that were in contact with the convex portions of the imprint mold, and this remaining portion is preferably removed before etching the synthetic quartz glass substrate. The method for removing the remaining portion is not particularly limited, and examples include ashing treatment using oxygen plasma, UV ozone treatment using ultraviolet light, and VUV treatment using vacuum ultraviolet light.

[0050] In the fourth step, the inorganic film pattern (hard mask pattern) is formed by selectively removing the inorganic film exposed by removing the organic film. Etching is suitable for selectively removing the inorganic film. Etching may be either a wet process or a dry process. In the wet process, an etching solution appropriate for the type of inorganic film is used. A specific example of a wet process is wet etching using a Cr etching solution (aqueous solution of cerium diammonium nitrate) when the inorganic film is Cr or a Cr compound. The concentration of the Cr etching solution is not particularly limited, but is preferably 5 to 20 mass %. On the other hand, anisotropic etching is suitable for a dry process. Specific examples of dry processes include argon ion milling and dry etching using reactive gases such as CF4, C3F6, C3F8, C4F8, C5F8, and CHF3. After the selective removal of the inorganic film, an organic film pattern usually remains on the inorganic film pattern. The fifth step may be carried out with this remaining organic film pattern left on the inorganic film pattern, or may be carried out after removing the organic film pattern from the inorganic film pattern.

[0051] In step 5, if the organic film pattern remains after the inorganic film is selectively removed in step 4, the surface of the synthetic quartz glass substrate is etched using the organic and inorganic film patterns (hard mask patterns) as an etching mask, or if the organic film pattern has been removed, using the inorganic film pattern (hard mask pattern) as an etching mask to form a pillar pattern region (plurality of nanopillars). In this etching, exposed portions of the synthetic quartz glass substrate surface that are not covered with the organic and inorganic film patterns or the inorganic film pattern are etched (digged in), and portions covered with the patterns remain unetched, thereby forming a pillar pattern region.

[0052] Methods for etching synthetic quartz glass substrates are not particularly limited, but examples include wet etching in which the substrate is immersed in an etching solution containing hydrofluoric acid or sodium fluoride, and dry etching using reactive gases such as CF, C3F6, C3F8, C4F8, C5F8, and CHF3.

[0053] In the sixth step, if the organic film pattern remains after the inorganic film is selectively removed in the fourth step, both the organic and inorganic film patterns are removed; if the organic film pattern is removed, the inorganic film pattern is removed. The organic film pattern can be removed simultaneously with the inorganic film pattern, and the inorganic film pattern can be removed by etching. Etching can be either a wet process or a dry process. In the wet process, etching is performed using an etching solution appropriate for the type of inorganic film. A specific example of a wet process is wet etching using a Cr etching solution (aqueous solution of cerium diammonium nitrate) when the inorganic film is Cr or a Cr compound. The concentration of the Cr etching solution is not particularly limited, but is preferably 5 to 20% by mass. On the other hand, anisotropic etching is suitable for a dry process. Specific examples of dry processes include argon ion milling and dry etching using reactive gases such as CF4, C3F6, C3F8, C4F8, C5F8, and CHF3.

[0054] So far, the method for manufacturing an individual authentication structure has been described by taking as an example a method in which an inorganic film is first formed on a synthetic quartz glass substrate and then an organic film is formed thereon, but the method is not limited to these embodiments. The individual authentication structure can also be manufactured by, for example, a so-called lift-off method in which an organic film is first formed on a synthetic quartz glass substrate, the organic film is patterned to form an organic film pattern, and then an inorganic film is formed thereon.

[0055] Specifically, this method includes, for example, (11) forming an organic film on the surface of the synthetic quartz glass substrate on which the pillar pattern region is to be formed (11th step); (12) A step of patterning the organic film to form an organic film pattern on the surface of the synthetic quartz glass substrate on which the pillar pattern region is to be formed (12th step); (13) forming an inorganic film on the organic film pattern and the exposed surface of the synthetic quartz glass substrate (13th step); (14) a step of removing the organic film pattern together with the inorganic film formed on the organic film pattern (14th step); (15) a step of etching the surface of the synthetic quartz glass substrate using an inorganic film pattern formed by an inorganic film formed on the surface of the synthetic quartz glass substrate as an etching mask to form a pillar pattern region (step 15); (16) Step of removing the inorganic film pattern (step 16) It can be produced by a method comprising:

[0056] In step 11, an organic film is formed on part or all of the surface of the synthetic quartz glass substrate on which the pillar pattern region is to be formed. The organic film is preferably made of a resist material (photoresist material) that is sensitive to a desired activation energy ray, such as an electron beam, X-ray, ultraviolet light, an excimer laser (ArF, KrF, etc.), or a high-pressure mercury lamp (i-line, g-line, etc.). While either a positive-type or negative-type resist material can be used as the resist material, positive-type resist materials are preferred from the viewpoints of precision and environmental friendliness. The thickness of the organic film can be selected from the range of 10 nm to several tens of μm, but a thin film is preferred from the viewpoint of resolution. In order to remove the organic film pattern together with the inorganic film in step 14, the organic film must be sufficiently thicker than the inorganic film (described later) (for example, at least twice as thick as the inorganic film).

[0057] The organic film can be formed by spin coating, spray coating, slit coating, etc., but spin coating is preferred for more uniform application. Spin coating is performed at a maximum rotation speed of 2,000 to 4,000 rpm, and baking (pre-baking) is performed after coating. The pre-baking temperature varies depending on the type of organic film material, but is preferably in the range of approximately 80 to 120°C.

[0058] In step 12, the organic film is patterned to form an organic film pattern on the surface of the synthetic quartz glass substrate where the pillar pattern region is to be formed. Methods for forming the organic film pattern include electron beam lithography or photolithography, and nanoimprint lithography.

[0059] In the electron beam lithography method, an organic film pattern can be formed by using an electron beam lithography device to write an organic film formed on a synthetic quartz glass substrate and developing the pattern written on the organic film.In the photolithography method, an organic film pattern can be formed by exposing an organic film formed on a synthetic quartz glass substrate using a photomask having predetermined light-shielding and non-light-shielding areas and developing the pattern transferred to the organic film.

[0060] The liquid used for development may be selected appropriately depending on the type of resist material. Suitable developers include, for example, aqueous alkaline solutions such as tetramethylammonium hydroxide (TMAH) and xylene-based organic solvents. After development, a rinse treatment with pure water or the like is performed to wash away any remaining developer and components derived from the resist material dissolved in the developer, followed by drying, thereby forming an organic film pattern on the synthetic quartz glass substrate. After drying, post-baking may be performed to strengthen the organic film. Post-baking is performed at a temperature and / or for a time period that makes the organic film insensitive to light, and is therefore preferably performed at a temperature higher than the pre-baking temperature before exposure (e.g., 130°C or higher).

[0061] In the nanoimprint lithography method, the concave-convex structure of an imprint mold having a predetermined concave-convex pattern is pressed against an organic film, the recesses of the mold are filled with a resist material, and the upper surface of the resist material is molded to have the shape of the concave-convex pattern.The organic film is hardened in this state, and then the imprint mold is separated from the hardened organic film, thereby forming an organic film pattern.

[0062] The concave-convex structure of the imprint mold is preferably pressed against the organic film under a helium gas atmosphere or a readily condensable gas atmosphere. A readily condensable gas atmosphere is a gas atmosphere that is easily liquefied by pressure when trapped in the mold voids. Such an atmosphere reduces the likelihood of bubble defects. Specific examples of such gases include 1,1,1,3,3-pentafluoropropane (PFP, HFC-245fa) and trans-1,3,3,3-tetrafluoropropene (TFP). Bubbles formed between the surface of the concave-convex structure of the imprint mold and the resist material can cause pattern defects in the organic film pattern. However, under a helium or readily condensable gas atmosphere, the helium gas or readily condensable gas that constitutes the bubbles dissolves into the resist material, preventing pattern defects. The organic film can be cured using a method appropriate for the curing type of the material that constitutes the organic film. For example, if the organic film material is UV-curable, a method such as irradiating the organic film with UV light via the imprint mold can be used.

[0063] After the imprint mold is separated from the cured organic film, a considerable thickness of the organic film (for example, 1 nm or more, particularly 5 nm or more, and 20 nm or less, particularly 10 nm or less) usually remains at the positions of the organic film that were in contact with the convex portions of the imprint mold, and this remaining portion is preferably removed before etching the synthetic quartz glass substrate. The method for removing the remaining portion is not particularly limited, and examples include ashing treatment using oxygen plasma, UV ozone treatment using ultraviolet light, and VUV treatment using vacuum ultraviolet light.

[0064] In step 13, an inorganic film is typically formed over the entire surface of the organic film pattern and the exposed synthetic quartz glass substrate. Examples of inorganic films include metal films and films of metal compounds such as metal nitrides, metal oxides, metal carbides, metal nitride oxides, metal nitride carbides, metal oxide carbides, and metal nitride oxycarbides. The metal film may be a simple film or an alloy film. Furthermore, the metal compound film may contain only one type of metal or a combination of two or more types. Specific examples of metals include Ag, Al, Au, Cr, Cu, Mo, Ni, Ru, Si, Ta, Ti, and W. Among these inorganic films, from the viewpoint of ease of etching in the etching of the inorganic film in step 16, Cr film, Si film, Cr compound film, and Si compound film are preferred, and specific examples of Cr compounds include CrN, CrO, CrNO, and CrNOC (these formulas represent the constituent elements of the compound, and the ratio of each element is arbitrary), and specific examples of Si compounds include SiN (this formula represents the constituent elements of the compound, and the ratio of each element is arbitrary), etc. The film thickness of the inorganic film is preferably 200 nm or less, more preferably 50 nm or less, and also preferably 10 nm or more.

[0065] The inorganic film can be formed by sputtering. Specifically, a metal target, a metal compound target, or the like is used as the target, and a rare gas such as argon gas, and optionally a reactive gas such as an oxygen-containing gas, a nitrogen-containing gas, or a carbon-containing gas, is used as the sputtering gas, and the inorganic film is formed on a synthetic quartz glass substrate in a sputtering apparatus. The power source may be either DC or AC, but when using a DC power source, it is preferable to apply measures to suppress arc generation.

[0066] In the fourteenth step, the organic film pattern is removed together with the inorganic film formed on the organic film pattern. If the organic film is formed to be sufficiently thicker than the inorganic film, the organic film pattern is removed from the side of the organic film pattern where the inorganic film is not formed, thereby removing only the inorganic film formed on the organic film pattern. In this case, the organic film pattern can be removed using an alkaline aqueous solution such as tetramethylammonium hydroxide (TMAH), a xylene-based organic solvent, or the like.

[0067] In the fifteenth step, the surface of the synthetic quartz glass substrate is etched using an inorganic film pattern (hard mask pattern) formed by an inorganic film formed on the surface of the synthetic quartz glass substrate as an etching mask to form a pillar pattern region (plurality of nanopillars). In this etching, the exposed surface portions of the synthetic quartz glass substrate that are not covered with the inorganic film pattern are etched (dug in), while the portions covered with the pattern remain unetched, forming the pillar pattern region.

[0068] Methods for etching synthetic quartz glass substrates are not particularly limited, but examples include wet etching in which the substrate is immersed in an etching solution containing hydrofluoric acid or sodium fluoride, and dry etching using reactive gases such as CF, C3F6, C3F8, C4F8, C5F8, and CHF3.

[0069] In the sixteenth step, the inorganic film pattern is removed. The inorganic film pattern can be removed by etching. Etching can be either a wet process or a dry process. In the wet process, etching is performed using an etching solution appropriate for the type of inorganic film. Specific examples of wet processes include wet etching using a Cr etching solution (aqueous solution of cerium diammonium nitrate) when the inorganic film is Cr or a Cr compound. The concentration of the Cr etching solution is not particularly limited, but is preferably 5 to 20 mass %. On the other hand, in the dry process, anisotropic etching is suitable. Specific examples of dry processes include argon ion milling and dry etching using reactive gases such as CF4, C3F6, C3F8, C4F8, C5F8, and CHF3. [Example]

[0070] EXAMPLES The present invention will be specifically explained below by showing examples and comparative examples, but the present invention is not limited to the following examples.

[0071] [Example 1] First, an imprint mold for use in nanoimprint lithography of organic films was prepared. A 10 nm thick CrN layer was formed by sputtering on a 20 mm × 20 mm, 0.525 mm thick square synthetic quartz glass substrate. A positive electron beam resist (ZEP520A, manufactured by Zeon Corporation) was then spin-coated onto the CrN layer and pre-baked at 180°C for 10 minutes to form an 80 nm thick positive electron beam resist layer. A conductive polymer charge-up inhibitor (Espacer 300Z, manufactured by Showa Denko K.K.) was then spin-coated to form a 10 nm thick antistatic layer.

[0072] Next, a circular hole pattern with a diameter of 100 nm was written using an electron beam lithography system (ELS-G125S, manufactured by Elionix Co., Ltd.). The antistatic layer was removed by rinsing with ultrapure water, and the substrate was immersed in a developer (ZED-N50, manufactured by Nippon Zeon Co., Ltd.) and then a rinse solution (ZMD-B, manufactured by Nippon Zeon Co., Ltd.) in that order, followed by drying, to form a circular resist hole pattern with a diameter of 100 nm on the CrN layer.

[0073] Next, an argon ion beam milling system (Hakuto Co., Ltd., 20IBE-C) was used to selectively remove the exposed surface of the CrN layer in the hole-shaped resist openings, forming a CrN mask pattern as a hard mask. The surface of the synthetic quartz glass substrate not covered by the CrN mask pattern was then etched using octafluoropropane (CF) gas using a dry etching system (Elionix Co., Ltd., EIS-200ER). The CrN mask pattern was then removed by immersion in a chrome etching solution (Hayashi Pure Chemical Industries, Ltd.), yielding a synthetic quartz glass imprint mold with a circular hole pattern with a diameter of 100 nm. A mold release agent, FAS13 ((tridecafluoro-1,1,2,2-tetrahydrooctyl)trimethoxysilane), was vapor-deposited onto the resulting imprint mold.

[0074] Next, a 10-nm-thick CrN film (inorganic film) was formed on a circular synthetic quartz glass substrate with a diameter of 100 mm and a thickness of 0.525 mm by sputtering. A photocurable resist was then applied to the CrN film to form an 80-nm-thick resist film (organic film). Next, a nanoimprinting system (ImpFlex Essential, manufactured by Sanmei Co., Ltd.) was used to press a release-agent-treated imprint mold against the substrate to form a resist film. The resist film was then cured in this state, forming a resist film pattern (organic film pattern) on the CrN film, which was a circular dot pattern with a diameter of 100 nm. The remaining resist film in areas other than the dot pattern was then removed using an oxygen reactive etching system (IM-TU01, manufactured by Tohoku University).

[0075] Next, an argon ion beam milling machine (Hakuto Co., Ltd., 20IBE-C) was used to selectively remove the exposed surface of the CrN film, except for the dot-patterned resist film pattern, to form a CrN mask pattern (inorganic film pattern) as a hard mask. Then, using octafluoropropane (CF) gas, a dry etching machine (Elionix Co., Ltd., EIS-200ER) was used to etch the surface of the synthetic quartz glass substrate that was not covered by the CrN mask pattern. The substrate was then immersed in a chrome etching solution (Hayashi Pure Chemical Industries, Ltd.) to remove the CrN mask pattern together with the resist film pattern, yielding a structure for individual authentication in which a pillar pattern region containing cylindrical nanopillars made of synthetic quartz glass was formed on the surface of the synthetic quartz glass substrate.

[0076] Figure 6 shows a scanning electron microscope image of the pillar pattern region of the resulting identity authentication structure. In this case, the nanopillar height H is 100 nm, the width (diameter) W is 100 nm, and the aspect ratio (H / W) is 1. The nanopillars are arranged in a regular rectangular lattice pattern with a nanopillar arrangement period of 500 nm. Meanwhile, the indentation modulus of the nanopillars in the pillar pattern region measured by nanoindentation was 87 GPa.

[0077] [Example 2] An identity authentication structure was obtained in the same manner as in Example 1, except that the diameter of the hole pattern formed in the imprint mold (the diameter of the dot pattern in the resist film pattern) was 50 nm. Figure 7 shows a scanning electron microscope image of the pillar pattern region of the identity authentication structure obtained. In this case, the height H of the nanopillars is 200 nm, the width (diameter) W is 50 nm, and the aspect ratio (H / W) is 4. The nanopillars are arranged in a regular, square lattice-like pattern, with an arrangement period of 250 nm. Meanwhile, the indentation elastic modulus of the nanopillars in the pillar pattern region measured by nanoindentation was 44 GPa.

[0078] [Example 3] A positive electron beam resist (ZEP520A, manufactured by Zeon Corporation) was spin-coated onto a 20 mm × 20 mm, 0.525 mm thick square synthetic quartz glass substrate and pre-baked at 180°C for 10 minutes to form an 80 nm thick positive electron beam resist film (organic film). A conductive polymer charge-up prevention agent (Espacer 300Z, manufactured by Showa Denko K.K.) was then spin-coated to form a 10 nm thick antistatic layer.

[0079] Next, an electron beam lithography system (ELS-G125S, manufactured by Elionix Corporation) was used to write a circular hole pattern with a diameter of 50 nm and an L-shaped line pattern as an origin mark. The antistatic layer was removed by washing with ultrapure water, and the substrate was immersed in a developer (ZED-N50, manufactured by Nippon Zeon Co., Ltd.) and then a rinse solution (ZMD-B, manufactured by Nippon Zeon Co., Ltd.) in that order, followed by drying to form a resist film pattern (organic film pattern) with a circular hole pattern with a diameter of 50 nm.

[0080] Next, a 10-nm-thick CrN film (inorganic film) was formed on the resist film by sputtering. The organic film pattern was then removed together with the inorganic film formed on the organic film pattern by immersion in toluene, and a CrN mask pattern (inorganic film pattern) was formed as a hard mask by lift-off. The surface of the synthetic quartz glass substrate not covered by the CrN mask pattern was then etched using a dry etching apparatus (Elionix, EIS-200ER) with octafluoropropane (CF) gas. The CrN mask pattern was then removed by immersion in a chrome etching solution (Hayashi Pure Chemical Industries, Ltd.), resulting in a structure for individual authentication in which a pillar pattern region containing cylindrical nanopillars formed of synthetic quartz glass was formed on the surface of the synthetic quartz glass substrate.

[0081] Figure 8 shows a scanning electron microscope image of the pillar pattern region of the resulting identity authentication structure. In this case, the nanopillar height H is 100 nm, the width (diameter) W is 50 nm, and the aspect ratio (H / W) is 2. The nanopillars are arranged in a regular, square lattice pattern with a nanopillar arrangement period of 250 nm. Meanwhile, the indentation modulus of the nanopillars in the pillar pattern region measured by nanoindentation was 62 GPa.

[0082] [Example 4] An identity authentication structure was obtained using the same method as in Example 3, except that the diameter of the hole pattern in the resist film pattern was 100 nm. Figure 9 shows a scanning electron microscope image of the pillar pattern region of the resulting identity authentication structure. In this case, the height H of the nanopillars is 300 nm, the width (diameter) W is 100 nm, and the aspect ratio (H / W) is 3. The nanopillars are arranged in a regular, square lattice-like pattern, with an arrangement period of 500 nm. Meanwhile, the indentation elastic modulus of the nanopillars in the pillar pattern region measured by nanoindentation was 47 GPa.

[0083] [Experimental Example 1] Using a nanoindentation tester (ENT-2100, manufactured by Elionix Co., Ltd.) equipped with a diamond spherical indenter (manufactured by Elionix Co., Ltd., radius of curvature 200 μm), the diamond spherical indenter (rigid body) was brought into contact with the pillar pattern region of the individual authentication structure produced in Example 1 and pressed into the pillar pattern region, thereby pressing some of the nanopillars formed in the pillar pattern region in the height direction and plastically deforming them. Specifically, the indenter was moved from the L-shaped origin mark at coordinates (X,Y) = (0,0) to coordinates (30,30), and pressed at a pressing speed of 5 mN / s with a load of 100 mN.

[0084] Figure 10 shows optical microscope images of the top surface of the nanopillars in the pillar pattern region. (A) is before plastic deformation, (B) is after plastic deformation, and (C) is an image of (B) that has been converted (binarized) for image analysis. The top image of the pillar pattern region shows that an elliptical impression has been formed, reflecting the curved shape of the indenter. Furthermore, image analysis using an image analysis tool revealed that the impression had a major axis of 9 μm, a minor axis of 6 μm, and a circularity of 0.76.

[0085] Figure 11 shows a scanning electron microscope image of the top surface of the pillar pattern region where the nanopillars were plastically deformed. The widths (diameters) of 25 nanopillars (5 vertical x 5 horizontal) in each of the regions A to E enclosed by dashed lines were measured. Regions B to E are located at positions where the nanopillar located at the center of each region is shifted by +12 nanopillars in the Y direction, +12 nanopillars in the X direction, -12 nanopillars in the Y direction, and -12 nanopillars in the X direction, respectively, relative to region A. The widths (diameters) of the nanopillars in region A were a minimum of 172 nm, a maximum of 188 nm, and an average of 179 nm. The widths (diameters) of the nanopillars in region B were a minimum of 118 nm, a maximum of 136 nm, and an average of 127 nm. The widths (diameters) of the nanopillars in region C were a minimum of 128 nm, a maximum of 158 nm, and an average of 143 nm. The width (diameter) of the nanopillars in region D was a minimum of 100 nm, a maximum of 134 nm, and an average of 114 nm. The width (diameter) of the nanopillars in region E was a minimum of 120 nm, a maximum of 138 nm, and an average of 130 nm. It was found that the width (diameter) of each nanopillar, which was 100 nm before plastic deformation, expanded after plastic deformation. It was also found that the width (diameter) of the nanopillars had a distribution among nanopillars within a region and also among regions.

[0086] Figure 12 shows atomic force microscope images of the nanopillars in the pillar pattern region after plastic deformation. (A) is a top view before plastic deformation, (B) is a cross-sectional profile before plastic deformation, (C) is a top view after plastic deformation, and (D) is a cross-sectional profile after plastic deformation. The heights of the four nanopillars (Nos. 1-4) before plastic deformation shown in Figures 12(A) and (B) were 106.09 nm, 105.87 nm, 105.94 nm, and 105.06 nm, respectively, which were almost identical to the set height of 100 nm. On the other hand, the heights of the three nanopillars (Nos. 1-3) after plastic deformation shown in Figures 12(C) and (D) were 50.36 nm, 50.92 nm, and 50.39 nm, respectively, indicating that the heights were approximately halved after plastic deformation. It was also found that the nanopillar heights varied among the nanopillars. As with the width (diameter) of the nanopillars described above, the distribution of the height of the nanopillars can also be confirmed between nanopillars within a given region and between regions.

[0087] [Comparative Example 1] An identity authentication structure was obtained using the same method as in Example 1, except that the dry etching time of the synthetic quartz glass was doubled. Figure 13 shows a scanning electron microscope image of the pillar pattern region of the obtained identity authentication structure. In this case, the height H of the nanopillars is 200 nm, the width (diameter) W is 100 nm, and the aspect ratio (H / W) is 2. The nanopillars are arranged in a regular, square lattice-like pattern, with an arrangement period of 500 nm. Meanwhile, the indentation modulus of the nanopillars in the pillar pattern region measured by nanoindentation was 31 GPa.

[0088] [Comparative Experiment Example 1] Using the structure for individual authentication produced in Comparative Example 1, some of the nanopillars formed in the pillar pattern region were pressed in the height direction and plastically deformed in the same manner as in Example 1.

[0089] Figure 14(A) is a scanning electron microscope image of the top surface of a portion of the pillar pattern where nanopillars were plastically deformed. It can be seen that the width (diameter) of the nanopillars, which was 100 nm before plastic deformation, expanded after plastic deformation. However, some nanopillars were chipped and fragments were scattered. Figure 14(B) is an image of Figure 14(A) that was converted (binarized) for image analysis. However, image analysis using an image analysis tool counted 54 nanopillars in the 5 x 5 area in the center of the image (total of 25 nanopillars), making it impossible to measure the nanopillar width (diameter), height, and their distribution. [Explanation of symbols]

[0090] 100 Synthetic quartz glass substrate 101 Pillar pattern area 102, 102a, 102b, 102c, 102d, 102e, 102f nanopillars

Claims

1. A structure for individual authentication, in which a pillar pattern region including a plurality of nanopillars formed of synthetic quartz glass is formed on at least a portion of a surface of a synthetic quartz glass substrate, Only the nanopillars are formed as microstructures protruding from a base portion of the synthetic quartz glass substrate on a surface portion of the synthetic quartz glass substrate, In the pillar pattern region, the indentation elastic modulus of the nanopillars measured by a nanoindentation method is 35 to 100 GPa; A structure for individual authentication, wherein the nanopillars undergo plastic deformation.

2. A structure for individual authentication, in which a pillar pattern region including a plurality of nanopillars formed of synthetic quartz glass is formed on at least a portion of a surface of a synthetic quartz glass substrate, The nanopillar has a cylindrical shape, an elliptical cylindrical shape, a truncated pyramid shape, a truncated cone shape, a truncated elliptical pyramid shape, an inverted truncated pyramid shape, an inverted truncated cone shape, or an inverted truncated elliptical pyramid shape, In the pillar pattern region, the indentation elastic modulus of the nanopillars measured by a nanoindentation method is 35 to 100 GPa; A structure for individual authentication, wherein the nanopillars undergo plastic deformation.

3. 3. The structure for individual authentication according to claim 1, wherein the arrangement of the nanopillars formed in the pillar pattern region is a regular arrangement in which the pillars are arranged at a constant period.

4. 4. The structure for individual authentication according to claim 3, wherein the period of the regular array is 20 nm or more and 1,500 nm or less.

5. 5. The structure for individual authentication according to claim 1, wherein the nanopillar has a height H of 20 to 1,500 nm, a width W of 10 to 500 nm, and an aspect ratio (H / W) of 0.5 to 6.

6. 6. The structure for individual authentication according to claim 1, wherein the nanopillars are formed integrally with a base portion of a synthetic quartz glass substrate.

7. 7. The structure for individual authentication according to claim 1, wherein a pillar pattern including plastically deformed nanopillars is utilized for identification.

8. A structure for individual authentication, in which a pillar pattern region including a plurality of nanopillars formed of synthetic quartz glass is formed on at least a portion of a surface of a synthetic quartz glass substrate, In the pillar pattern region, the indentation elastic modulus of the nanopillars measured by a nanoindentation method is 35 to 100 GPa; A structure for individual authentication, characterized in that the pillar pattern region includes nanopillars that have been pressed in the height direction and plastically deformed.

9. 9. The structure for individual authentication according to claim 8, wherein the nanopillars are formed integrally with a base portion of a synthetic quartz glass substrate.

10. A method for manufacturing the structure for individual authentication according to any one of claims 1 to 7, comprising the steps of: forming an inorganic film on a surface of a synthetic quartz glass substrate on which the pillar pattern region is to be formed; forming an organic film on the inorganic film; patterning the organic film to form an organic film pattern on the inorganic film; forming an inorganic film pattern by etching the inorganic film using the organic film pattern as an etching mask; a step of etching a surface portion of the synthetic quartz glass substrate using the organic film pattern and / or the inorganic film pattern as an etching mask to form the pillar pattern region; removing the organic film pattern and / or the inorganic film pattern; A method for manufacturing an individual authentication structure, comprising:

11. A method for manufacturing the structure for individual authentication according to any one of claims 1 to 7, comprising the steps of: forming an organic film on a surface of the synthetic quartz glass substrate on which the pillar pattern region is to be formed; patterning the organic film to form an organic film pattern on a surface of the synthetic quartz glass substrate on which the pillar pattern region is to be formed; forming an inorganic film on the organic film pattern and the exposed surface of the synthetic quartz glass substrate; removing the organic film pattern together with an inorganic film formed on the organic film pattern; a step of etching a surface portion of the synthetic quartz glass substrate using an inorganic film pattern formed by an inorganic film formed on a surface of the synthetic quartz glass substrate as an etching mask to form the pillar pattern region; removing the inorganic film pattern A method for manufacturing an individual authentication structure, comprising:

12. The method according to claim 10 or 11, wherein in the step of forming the organic film pattern, the organic film pattern is formed by electron beam lithography, photolithography or nanoimprint lithography.

Citation Information

Patent Citations

  • Production method of structure for individual authentication

    JP2014059377A

  • Display body having fine concavo-convex diffraction structure

    JP2014238465A

  • Transparent observation substrate, observation container and manufacturing method therefor, method of polishing transparent base material, and observation method

    JP2016118635A

  • Individual authentication semiconductor chip, individual authentication medium and method to authenticate individual

    JP2018089845A

  • Spectrometer using diffraction lattice

    WO2004027493A1